2019
DOI: 10.1371/journal.pone.0214095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improved attenuation correction on 18F-FDG PET/MR hybrid imaging of the heart

Abstract: PurposeThe aim of this study was to evaluate and quantify the effect of improved attenuation correction (AC) including bone segmentation and truncation correction on 18F-Fluordesoxyglucose cardiac positron emission tomography/magnetic resonance (PET/MR) imaging.MethodsPET data of 32 cardiac PET/MR datasets were reconstructed with three different AC-maps (1. Dixon-VIBE only, 2. HUGE truncation correction and bone segmentation, 3. MLAA). The Dixon-VIBE AC-maps served as reference of reconstructed PET data. 17-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In recent clinical studies on whole-body PET/MR investigating oncologic patients injected with 18 F-FDG as radiotracer, it was shown that improved AC including a bone model and methods for truncation correction showed robust results and MR-based truncation correction provided realistic body contours [11,12,20]. In contrast to these previous studies, the improved AC method in the present study was applied to a patient collective with bone lesions and that was injected with four different radiotracers ( 18 F-FDG, 68 Ga-DOTATOC, 68 Ga-PSMA, and 124 I-MIBG).…”
Section: Discussionmentioning
confidence: 99%
“…In recent clinical studies on whole-body PET/MR investigating oncologic patients injected with 18 F-FDG as radiotracer, it was shown that improved AC including a bone model and methods for truncation correction showed robust results and MR-based truncation correction provided realistic body contours [11,12,20]. In contrast to these previous studies, the improved AC method in the present study was applied to a patient collective with bone lesions and that was injected with four different radiotracers ( 18 F-FDG, 68 Ga-DOTATOC, 68 Ga-PSMA, and 124 I-MIBG).…”
Section: Discussionmentioning
confidence: 99%
“…For the PET acquisition and reconstruction in PET/MR, recommendations (95). In general, the use of attenuation correction methods incorporating bone should be encouraged when they become available (96). When available, the use of free-breathing radial VIBE sequences for AC is encouraged since these AC sequences appear to reduce breathing and motion artifacts (97).…”
Section: Pet/mr Procedurals In 4ismentioning
confidence: 99%
“…Currently commercially available Dixon-based MR-based attenuation correction methods using four tissue class segmentation are preferred for [ 18 F]FDG quantification ( 94 ) and have been shown to yield quantitatively comparable results as PET/CT for perfusion imaging with [ 15 O]water ( 95 ). In general, the use of attenuation correction methods incorporating bone should be encouraged when they become available ( 96 ). When available, the use of free-breathing radial VIBE sequences for AC is encouraged since these AC sequences appear to reduce breathing and motion artifacts ( 97 ).…”
Section: Pet/mr Procedurals In 4ismentioning
confidence: 99%
“…Additional variability can arise from different PET reconstruction parameters, registration algorithms, FOV truncation compensation, MR‐coils, SUV error types (mean vs maximum or whole‐lung vs a voxel basis), and patient diseases. A better consensus and more lung‐specifically targeted studies would be of great benefit for future applications of lung PET/MRI.…”
Section: Potential Future Strategiesmentioning
confidence: 99%